Luminescent materials as spectral converters: Power dependent profiling of solid NaYF4:Yb3+, Er3+ UCNP reveals highly efficient UVA–Blue emission - Bujjamer, Juan M. (2019)
Upconversion is a common process in lanthanides-based materials in which absorption of multiple low energy photons result in a high energy one. The emission spectrum is frequently tuned by changing the composition of the material. However, a commonly overlooked aspect is the non-linear power dependence which can influence the spectral and temporal properties of the emission. Moreover, as upconverting materials have been shown to increase the output current density in photovoltaic cells when used as spectral converters, the complete power profile is required to calculate the improved efficiency and needs to be incorporated in the design process. In this work, we show that solid β-NaYF4:Yb3+, Er3+upconversion nanoparticles, well known for the green?red emission, can also emit efficiently in the UVA?blue range. These bands are often neglected in the literature in nanosized particles despite having promising applications. In addition, we characterized their stationary and dynamic luminescence features as a function of incident power to reveal the relevant intra-band mechanisms. Our results demonstrate that the red emission at high incident power is explained by back-energy transfer. Finally, by simultaneously acquiring time resolved decays and power dependent emission slopes, we classified the spectral information to build a visual summary of the system providing a description at a glance of its complex dynamics.